Changing the name of the NBPF/DUF1220 domain to the Olduvai domain - Sikela, James M. (F1000Res, 2018)
We are jointly proposing a new name for a protein domain of approximately 65 amino acids that has been previously termed NBPF or DUF1220. Our two labs independently reported the initial studies of this domain, which is encoded almost entirely within a single gene family. The name Neuroblastoma Breakpoint Family ( NBPF) was applied to this gene family when the first identified member of the family was found to be interrupted in an individual with neuroblastoma. Prior to this discovery, the Pfam database had termed the domain DUF1220, denoting it as one of many protein domains of unknown function. It has been Pfam’s intention to use “DUF” nomenclature to serve only as a temporary placeholder until more appropriate names are proposed based on research findings. We believe that additional studies of this domain, primarily from our laboratories over the past 10 years, have resulted in furthering our understanding of these sequences to the point where proposing a new name for this domain is warranted. Because of considerable data linking the domain to human-specific evolution, brain expansion and cognition, we believe a name reflecting these findings would be appropriate. With this in mind, we have chosen to name the domain (and the repeat that encodes it) Olduvai. The gene family will remain as NBPF for now. The primary domain subtypes will retain their previously assigned names (e.g. CON1-3; HLS1-3), and the three-domain block that expanded dramatically in the human lineage will be termed the Olduvai triplet. The new name refers to Olduvai Gorge, which is a site in East Africa that has been the source of major anthropological discoveries in the early-mid 1900’s. We also chose the name as a tribute to the scientists who made important contributions to the early studies of human origins and our African genesis.